Comparison of antispasmodic effect of hydroalcoholic extract of Dracocephalum kotschyi Boiss. in rat uterus and ileum - Hassan Sadraei; Gholamreza Asghari; Mahla Alinejad (Research in Pharmaceutical Sciences, 2016)
Dracocephalum kotschyi Boiss. is a traditional medicine with antispasmodic activities. The objective of this research was to study antispasmodic activities of hydroalcoholic extract of D. kotschyi on rat isolated uterus contractions for comparison with isolated ileum. Hydroalcoholic extract was obtained from aerial part of D. kotschyi using percolation method. A portion of rat ileum or uterus was suspended in Tyrode′s solution at 37 °C and gassed with O 2 . Effect of D. kotschyi extract was assessed on ileum or uterus contractions induced by KCl (80 mM), acetylcholine (ACh, 500 nM), electrical field stimulation (EFS) or oxytocin (0.0005 IU/mL). The extract of D. kotschyi concentration-dependently inhibited ileum responses to KCl (IC 50 = 65 ± 18 μg/mL), ACh (IC 50 = 102 ± 18 μg/mL) and EFS (IC 50 = 117 ± 29 μg/mL). The extract of D. kotschyi also concentration-dependently inhibited uterus responses to KCl (IC 50 = 453 ± 64μg/mL), ACh (IC 50 = 58 ± 9 μg/mL), EFS (IC 50 = 22 ± 3 μg/mL) as well as oxytocin (IC 50 = 70 ± 11 μg/mL). From this experiment it was concluded that D. kotschyi extract possesses antispasmodic activities on both smooth muscle of ileum and uterus. In comparison, the extract was more effective inhibitor of ACh and EFS responses in rat uterus than on the ileum. On the other hand, the extract was a more potent inhibitor of KCl response on rat ileum. However, the extract was found to be a potent inhibitor of oxytocin-induced contraction of rat uterus. These results indicate that D. kotschyi extract may contain components that might be useful lead compounds for prevention of uterus spasm.